DEHYDRATION PROCESSES AND MORPHOLOGICAL CHARACTERISTICS OF NATURAL GYPSUM MINERALS FROM THE USTYURT PLATEAU, REPUBLIC OF KARAKALPAKSTAN - Mnazhov A. N.; Abylova A. Zh.; Turganbaeva T. D. (Journal Park Publishing, 2025)
This paper investigates the thermal and morphological characteristics of natural gypsum minerals collected from the Ustyurt Plateau, Republic of Karakalpakstan. Three gypsum samples were selected as the objects of study. The dehydration processes of the gypsum minerals were examined using differential thermal analysis (DTA) and thermogravimetric analysis (TGA). The microstructural characteristics were analyzed by scanning electron microscopy (SEM). The obtained data provide a basis for evaluating the thermal behavior and microstructural features of the gypsum minerals and can be used for further studies aimed at optimizing their processing conditions.
Keywords: Ustyurt Plateau, gypsum mineral, dehydration process, thermogravimetric analysis, differential thermal analysis, scanning electron microscopy, morphology, thermal stability.